2022
DOI: 10.1002/cam4.5068
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic compounds activate MAPK and inhibit Akt pathways to induce apoptosis in MA‐10 mouse Leydig tumor cells

Abstract: Arsenic compounds have been applied treating acute promyelocytic 1eukemia and solid tumors with brief mechanism investigations. In fact, we have demonstrated that sodium arsenite plus dimethylarsenic acid could activate apoptosis in MA‐10 mouse Leydig tumor cells by inducing caspase pathways. However, detail underlying mechanisms how caspase cascade is regulated remains elusive. Therefore, the apoptotic mechanism of sodium arsenite plus dimethylarsenic acid were examined in MA‐10 cells in this study. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Studies have shown MAPK signaling pathways are involved to regulate cell survival, differentiation, gene expression, proliferation, mitosis and/or apoptosis ( 21 24 ). To test if MAPK pathways were associated with apoptosis induced by arsenic compounds in OC3 cells, JNK, ERK1/2 and p38 phosphorylation was analyzed with western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown MAPK signaling pathways are involved to regulate cell survival, differentiation, gene expression, proliferation, mitosis and/or apoptosis ( 21 24 ). To test if MAPK pathways were associated with apoptosis induced by arsenic compounds in OC3 cells, JNK, ERK1/2 and p38 phosphorylation was analyzed with western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptotic cascades are regulated by a number of cellular signal transduction pathways and the MAPK signaling pathway is one associated with cellular stress ( 15 , 16 , 21 24 ). It has been shown that MAPK signaling pathways can enhance cell survival or promote sensitivity to apoptosis, which depends on different stimuli, cell types and activation latency ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVDF membrane with transferred protein was incubated in blocking buffer (5% non-fat milk in 0.1% TBST washing buffer) for 1 h and incubated with primary antibodies for 16–18 h at 4 °C. Membranes were washed 3 times with TBST and incubated with the appropriate dilution of HRP-conjugated secondary antibodies for 1 h. Signaling was visualized through UVP EC3 BioImaging Systems (UVP, Upland, CA, USA) by ECL detection kit [ 38 ]. The quantificational analysis was analyzed with ImageJ program version 1.5 (NIH, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%